OPTIMIZING DYE REMOVAL FROM TEXTILE WASTEWATER USING TWO STAGES COAGULATION - SARTIKA PUTRI (NIM 15306046); Pembimbing: Dr.Ing. Prayatni Soewondo, MS., AGUSTINE
Wastewater from textile industries consist of dye which is used for dyeing and printing the fabrics. Most of dye types commonly used are reactive azo such as Remazol Red RB 133 which is used in this research. It was undegradable and can caused pollution if it was disposed without a treatment. This research done to treat dyes wastewater with Two Stages Coagulation. It is a kind of process which coagulant added and rapid mixing were done two times and followed with a flocculation process (Dewi, 2008) . Two stages coagulation is one of water treatment alternatives by coagulation especially for water treatment with high color and organic matter (Carlson et al,2000). Because of mineral variaty in the water, some conventional coagulation are often not success to remove them, so it necessary to get an optimum condition of coagulation.The efficiency of Poly Aluminium Chloryde (PAC) in discoloration of dying wastewater has been investigated with the Jartest methode.The results show that optimum dosage of one stage coagulation was 0,2 mg/L at pH 9, the efficiency of removal color reaches 98,11%. While the optimum dosage of Two Stages Coagulation is 0,16mg/L, lower than One Stage Coagulation so that the consumption of PAC can be minimazed. The color removal efficiency reaches 100% by dividing coagulant added 50% of dosage for the first stage and the 50% other for the second stage, The pH adjustmet for the first stage before coagullant added was 5 (acid condition) and then pH should be incresed till 9 for the second stage. But, for overall the neutral condition (pH 7) give the optimum performance for color removal. But initially, when the initial pHis neutral for both stages, the two stages coagulation gives the best performance to color removal.